Determinants of Islamic Banking Profitability: A Comparative Analysis of Indonesia and Malaysia - Syifa Nurmilla Fathiyyah; Muhammad Muflih (Universitas Airlangga, 2023)
ABSTRACT Islamic banking in Indonesia and Malaysia experienced differences in asset growth and market share, potentially causing dissimilarity in profitability performance. This study aims to evaluate the factors that influence the increase in profitability of Islamic banking in Indonesia and Malaysia using signaling theory including market concentration (HHI), company size and financing risk (NPF), and national income (GDP) as control variables. It analyzed the Indonesian and Malaysian Islamic banks during the period 2017-2021. The method used in this study is comparative descriptive with panel data regression analysis measuring instruments. Based on the results of empirical analysis, factors that affect the profitability of Islamic banking in Indonesia are financing risk, while in Malaysia, it is financing risk and national income. The results of this study update the view on the profitability of Islamic banking in Indonesia and Malaysia. In addition, from the managerial side, this study contributes to creating NPF control in Indonesian Islamic banking because these factors can increase the profitability of the country's Islamic banking. The study also contributes to the development of market concentration strategies, company size, and financing risks in Malaysian Islamic banking as all these factors can increase the profitability of the country's Islamic banking. Keywords: Islamic Banking, Profitability, Market Concentration, Company Size, Financing Risk ABSTRAK Perbankan syariah Indonesia dan Malaysia mengalami perbedaan dalam pertumbuhan aset dan market share sehingga berpotensi menimbulkan perbedaan kinerja profitabilitas. Studi ini bertujuan untuk mengevaluasi faktor yang mempengaruhi peningkatan profitabilitas perbankan syariah di Indonesia dan Malaysia dengan menggunakan signaling theory diantaranya konsentrasi pasar (HHI), ukuran perusahaan dan risiko pembiayaan (NPF) serta pendapatan nasional (GDP) sebagai variabel kontrol. Studi ini menganalisis bank syariah di Indonesia dan Malaysia selama periode 2017-2021. Metode yang digunakan oleh studi ini adalah komparatif deskriptif dengan alat ukur analisis regresi data panel. Berdasarkan hasil analisis empiris, faktor yang mempengaruhi profitabilitas perbankan syariah Indonesia adalah risiko pembiayaan sedangkan di Malaysia adalah risiko pembiayaan serta pendapatan nasional. Hasil penelitian ini memperbaharui pandangan tentang profitabilitas perbankan syariah Indonesia dan Malaysia. Selain itu dari sisi manajerial, studi ini berkontribusi dalam menciptakan pengendalian NPF pada perbankan syariah Indonesia karena faktor tersebut mampu meningkatkan profitabilitas perbankan syariah negara tersebut. Selain itu studi ini juga berkontribusi dalam pengembangan strategi konsentrasi pasar, ukuran perusahaan dan risiko pembiayaan pada perbankan syariah Malaysia karena semua faktor tersebut mampu meningkatkan profitabilitas perbankan syariah negara tersebut. Kata Kunci: Bank Syariah, Profitabilitas, Konsentrasi Pasar, Ukuran Perusahaan, Risiko Pembiayaan